Penentuan Siswa Terbaik Dengan Metode Simple Additive Weighting (SAW) Dalam Sistem Informasi Akademik Berbasis Android Di Paud Delima Vii Bekasi - Furqan, Muhammad; Gunawan, Dedi (JUKI : Jurnal Komputer dan Informatika, 2023)
The Study discusses implementation the method Simple Additive Weight (SAW) in the android based academic information system in Paud Delima VII Bekasi to determine the best student and provide information relating to the academic. This information system in use to facilitate student academic data management and assist in decision making regarding student achievement assessments and specify the best student. In this study an android information system was developed to allow users to input and manage student data, such as test score, academic achievements, attendance levels, and other attributes that are relevant and will be used as criteria in determining the best students. The Simple Additive Weight (SAW) method is used to assess and provide weight that reflect levels of consistent interest in determining the best student assessment criteria. After weight is given, the system will be calculate the total value of each student by the corresponding value criteria. The highest total student will be regarded as the best. The Simple Additive Weight (SAW) is selected because of its strengths in combining various criteria on a priority scale.